National and subnational HIV/AIDS coordination: are global health initiatives closing the gap between intent and practice? - Spicer, Neil (BioMed Central, 2010)
BACKGROUND: A coordinated response to HIV/AIDS remains one of the 'grand challenges' facing policymakers today. Global health initiatives (GHIs) have the potential both to facilitate and exacerbate coordination at the national and subnational level. Evidence of the effects of GHIs on coordination is beginning to emerge but has hitherto been limited to single-country studies and broad-brush reviews. To date, no study has provided a focused synthesis of the effects of GHIs on national and subnational health systems across multiple countries. To address this deficit, we review primary data from seven country studies on the effects of three GHIs on coordination of HIV/AIDS programmes: the Global Fund to Fight AIDS, Tuberculosis and Malaria, the President's Emergency Plan for AIDS Relief (PEPFAR), and the World Bank's HIV/AIDS programmes including the Multi-country AIDS Programme (MAP). METHODS: In-depth interviews were conducted at national and subnational levels (179 and 218 respectively) in seven countries in Europe, Asia, Africa and South America, between 2006 and 2008. Studies explored the development and functioning of national and subnational HIV coordination structures, and the extent to which coordination efforts around HIV/AIDS are aligned with and strengthen country health systems. RESULTS: Positive effects of GHIs included the creation of opportunities for multisectoral participation, greater political commitment and increased transparency among most partners. However, the quality of participation was often limited, and some GHIs bypassed coordination mechanisms, especially at the subnational level, weakening their effectiveness. CONCLUSIONS: The paper identifies residual national and subnational obstacles to effective coordination and optimal use of funds by focal GHIs, which these GHIs, other donors and country partners need to collectively address.